DETERMINAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA HASIL PEMEKARAN DI PROVINSI JAMBI - Agriend. S. Putra (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The research aims to find out the determine and examine the effect of capital expenditure, investment and labor on the economic growth of regencies / cities as a result of the division in Jambi Province in 2010-2017. The data used in this study are secondary data, in the form of 2010-2017 time series and cross sections (5 districts and cities resulting from the division in Jambi Province). The analytical tool used is panel data with the help of Eviews 10 and using the Fixed Effect Model. The results of this study show the following: the independent variables in this case capital expenditure, investment and labor simultaneously affect the dependent variable, namely economic growth, by showing an F-Statistic value of 6.502578 with a probability of 0.000083 which means smaller from alpha 0.05 (α <0.05). Capital expenditures and investments with a coefficient of -0.796238 (probability 0.0007) and 2.144898 (probability 0.0001), respectively, are concluded as having an effect on the economic growth of regencies / cities as a result of the division in Jambi Province. While the labor coefficient value of 7.617456 (probability 0.5918) concluded had no effect on the economic growth of regencies / cities as a result of the division in Jambi Province